A democracia direta como política para a expansão das capacitações e promoção do desenvolvimento humano - Ferrer, Francisco Pozzobon (2019)
Democracy has fundamental values for human development: it allows the political participation of citizens, the conceptualization of needs and the accountability of representatives. Direct democracy has the potential to expand these values, increasing the channels of interlocution between citizens and governments. The objective of this study is to examine whether direct democracy, used for more than 100 years as a complement to representative democracy, is a good policy for human development, according to the capabillities approach, and to see if its potential is actually reached. To this end, the potential of direct democracy is presented in terms of the expansion of fundamental values, the citizens’ agency and the promotion of public reason. Then the mechanisms of direct democracy and their expected effects by theory are presented. Then examples are shown where the potential of direct democracy is observed. Finally, comparisons are presented between US states that allow and do not allow initiatives regarding a human development index and a measure of poverty. This study demonstrates that the potential of direct democracy exists. On the one hand, positive, by expanding the fundamental values of democracy, increasing citizens’ agency and promoting public reason. On the other hand, negative, by allowing the majority of the population to restrict political minority rights. The study also shows that initiatives are likely to have a positive impact on people’s life expectancy, even though it has no effects on income and poverty.